PENGARUH FINANCIAL LITERACY DAN PENDAPATAN TERHADAP SAVING BEHAVIOR ORANG TUA MAHASISWA - jessica claudia irawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Saving is an activity to keep a portion of income which is not planned to be spent. Saving activity relates to saving behavior. Saving behavior is a decision making activity regarding routine activity to save some part of income for a purpose in the future. This study aims to determine the effect of financial literacy and income on the saving behavior of parents of students related to education plans. The population were parents of students of several private universities in Surabaya. These private universities consist of Petra Christian University, Ciputra University, and Surabaya University. The research sample is 100 respondents. Data were collected by distributing questionnaires on google forms and distributed through social media such as Instagram, LINE, and Whatsapp. This research uses Partial Least Square (PLS) data analysis method. The research results show that Financial Literacy and Income have a significant effect on Saving Behavior.